Little is logical - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Joining farmers' experiments edited by Bertus Haverkort, Johan van der Kamp and Ann Waters-Bayer 1991 269pp UKL9.95 ISBN 1 85399101 8